A dictionary of climate change and the environment economics, science, and policy - Quentin Grafton (Northampton Edward Elgar, 2012)
A Dictionary of Climate Change and the Environment bridges the gap between the many disciplines encompassing climate change, environmental economics, environmental sciences, and environmental studies.
Includes bibliographical references (p. 375-383).
Keywords: Environmental economics--Dictionaries.